Examining Collaborative Learning’s Influences On Fifth Grade EFL Student’s English Proficiency - Erliani, Windia; Zasrianita, Fera; Andriadi, Andriadi (ELT Worldwide: Journal of English Language Teaching, 2025)
This study investigates the impact of collaborative learning on the English proficiency of fifth-grade EFL students at SDN 60 Bengkulu Utara. Employing a quantitative one-group pre-test–post-test design, data were collected from 24 students using a standardized English proficiency test that assessed vocabulary, reading, writing, speaking, and grammar skills. Pre-test results revealed that 79.2% of students were in the “low” category and 12.5% in the “very low” category. Following the implementation of collaborative learning, post-test results showed a marked improvement, with 66.7% of students achieving the “high” category and 33.3% the “very high” category, and none remaining in the lower categories. The mean score rose significantly from 39.58 to 72.13. A paired-sample t-test confirmed the statistical significance of this improvement (p<0.05). These findings demonstrate that collaborative learning substantially enhances the English proficiency of young learners, not only raising academic achievement but also fostering motivation, participation, and teamwork. The study underscores the effectiveness of collaborative learning in resource-limited rural schools, offering empirical support for its broader integration into elementary EFL instruction.